Varamientos de mamíferos marinos en la costa continental ecuatoriana período 1987 - 1995. - Chiluiza, D.; Aguirre, W.; Félix, F.; Haase, B. (Instituto Oceanográfico de la Armada, Guayaquil, Ecuador, 1998)
Between 1987 and 1995, 93 strandings of marine mammals were recorded along the ecuadorian continental coast, including one mass stranding of 56. The strandings involved 12 species of cetaceans (10 Odontoceti and 2 Mysticeti) and one species of pinniped. The Odontoceti were represented by: bottlenose dolphin Tursiops truncatus (n=30), sperm whale Physeter macrocephalus (n=25), Pacific spotted dolphin Stenella attenuata (n=7), striped dolphin Stenella coeruleoalba (n=2), false killer whale Pseudorca crassidens (n=2), Cuvier's beaked whale Ziphius cavirostris (n=2), short finned pilot whale Globicephala macrorhynchus (n=1), short-beaked common dolphin Delphinus delphis (n=3), Risso's dolphin Grampus griseus (n=1) and pygmy killer whale Feresa attenuata (n=1). The Mysticeti were represented by: Bryde's whale Balaenoptera edeni (n=2) and humpback whale Megaptera novaeangliae (n=4). Two other species were identified at genus level only. The pinniped recorded was the south American sea lion Otaria flavescens (n=11). This report includes the first records of two species in ecuadorian coastal waters. Incluye ref.bibl., ilus., tbls. Published